Extensive quantum chemistry study of neutral and charged C4N chains: anattempt to aid astronomical observations - Bâldea, Ioan (ACS earth and space chemistry, 2020)
Many molecular species can presumably still be observed in space if they are adequately characterized chemically. In this paper, we suggest that this could be the case of the neutral (C4N0) and anion (C4N-) cyanopropynylidene chains, which were not yet identified in space although both the neutral (C3N0 and C5N0) and anion (C3N- and C5N-) neighboring members of the homologous series were observed. Extensive data obtained from quantum chemical calculations using density functional theory (DFT), coupled-cluster (CC), and quadratic configuration interaction (QCI) methods for all charge and spin states of interest for space science (doublet and quartet neutrals, triplet and singlet anions, and singlet and triplet cations) are reported, e.g., bond metric and natural bond order data, enthalpies of formation, dissociation and reaction energies, spin gaps, rotational constants, vibrational properties, dipole and quadrupole moments, electron attachment energies (EAs), and ionization potentials (IPs). The fact that (not only for C4N but also for C2N and C6N) the quantum chemical methods utilized here are able to excellently reproduce the experimental EA value, which is often a challenge for theory, is particularly encouraging, since this indicates that theoretical estimates of chemical reactivity indices (which are key input parameters for modeling astrochemical evolution) can be trusted. The presently calculated enthalpies of formation and dissociation energies do not substantiate any reason to assume that C4N is absent in space. To further support this idea, we analyze potential chemical pathways of formation of both C4N0 and C4N-, which include association and exchange reactions. In view of the substantially larger dipole moment (Danion ≫ Dneutral), we suggest that astronomical detection should first focus on C4N- chains rather than on neutral C4N0 chains.
Gesehen am 03.12.2020
Im Titel ist die Ziffer "4" tiefgestellt